Pemanfaatan Teknologi Digital dan Dukungan Perusahaan terhadap Adaptasi Karyawan dengan Resiliensi Karyawan sebagai Variabel Moderasi pada PT. Bahtera Agung Medan - Michelyn Leonid; Huliman Huliman; Devi Devi (Institut Nalanda, 2026)
This study aims to analyze the influence of Digital Technology Utilization and Company Support on Employee Adaptation, with Employee Resilience as a moderating variable at PT. Bahtera Agung Medan. This study used quantitative methods. The population in this study was all employees of PT. Bahtera Agung Medan, with a sample of 58 respondents determined using census sampling techniques. The data analysis techniques used were multiple linear regression and Moderated Regression Analysis (MRA). The results showed that all research instruments were valid and reliable. The classical assumption test indicated that the data were normally distributed, free from multicollinearity and heteroscedasticity. Partially, Digital Technology Utilization influenced Employee Adaptation at PT. Bahtera Agung Medan. Company Support also influenced Employee Adaptation at PT. Bahtera Agung Medan. Simultaneously, Digital Technology Utilization and Company Support influenced Employee Adaptation at PT. Bahtera Agung Medan. However, Employee Resilience did not moderate the effect of Digital Technology Utilization on Employee Adaptation at PT. Bahtera Agung Medan. Furthermore, Employee Resilience also failed to moderate the effect of Company Support on Employee Adaptation at PT. Bahtera Agung Medan. The results of this study are expected to provide consideration for companies in improving employee adaptability through optimal use of digital technology and company support.